2022
DOI: 10.1371/journal.pone.0272288
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal effect of faba bean fractions in WD-fed mice treated with low dose of DSS

Abstract: Rodent studies have shown that legumes can reduce chemical induced colonic inflammation, but the role of faba bean fractions for colon health has not been described. We have investigated the role of protein and fiber fractions of faba beans for colonic health and microbiota composition in a low-grade inflammation mice-model when incorporated in a Western diet (WD). The diet of sixty C57BL/6JRj male mice was standardized to a WD (41% fat, 43% carbohydrates) before were randomly assigned to four groups (n = 12) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Then, they were cultured in a serum‐free medium and treated with EVs (2 × 10 8 particles/ml) for up to 72 h (Li et al 2019). The mRNA expressions of ACTA2 and Col1A1 were detected using quantitative real‐time PCR (qRT‐PCR) (Papoutsis et al 2022). GAPDH was used as the internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Then, they were cultured in a serum‐free medium and treated with EVs (2 × 10 8 particles/ml) for up to 72 h (Li et al 2019). The mRNA expressions of ACTA2 and Col1A1 were detected using quantitative real‐time PCR (qRT‐PCR) (Papoutsis et al 2022). GAPDH was used as the internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Faba beans are known to be rich in proteins and contain abundant dietary fibers that could contribute to anti-IBD activities through modulating gut microbiota and preventing gut dysbiosis. 51,52 A previous study conducted by Papoutsis et al 53 investigated the role of protein and fiber fractions of faba beans for colonic health and microbiota composition in a low-grade inflammation mouse model. They found that faba bean fractions had minor effects on inflammatory parameters and colonic microbiota.…”
Section: Food and Function Papermentioning
confidence: 99%